Mannose-binding lectin and its genetic variants - Garred, Peter (2006)
Mannose-binding lectin (MBL) is a collagen-like serum protein that mediates activation of the complement system and is of importance for host defence. Common variant alleles situated both in the promoter and structural region of the human MBL gene (MBL2) influence the stability and the serum concentration of the protein. Epidemiological studies have suggested that genetically determined variation in MBL serum concentration influences the susceptibility to and the course of different types of infections, autoimmune, metabolic and cardiovascular diseases, but this is still a subject of debate. The fact that these genetic variations are very frequent indicates a dual role for MBL in host defence. In this survey, we summarize the current molecular understanding of human MBL genetics.